Efficacy and safety of ferric carboxymaltose in Indian pregnant women with iron deficiency anemia - Bhat, Vidya; Kiran, Brunda; Deshmukh, Girish; Kulkarni, Ketan; Rodge, Ajinkya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Iron deficiency anemia (IDA) is a significant problem worldwide particularly in women. The aim of the study was to evaluate the effectiveness of intravenous ferric carboxymaltose (FCM) in in Indian pregnant women with anemia. Method: This was a single centre, prospective, observational, open label, clinical study at real life scenario with 4 weeks follow up. Fifty pregnant women with IDA and visiting to the Radhakrishna multispecialty hospital, Bangalore, for antenatal care were enrolled for the study. IV FCM was given as per the standard protocol. Change in the laboratory parameters such as hemoglobin, mean corpuscular volume (MCV), mean corpuscular hemoglobin concentration (MCHC), packed cell volume (PCV) level at baseline and after 4 weeks of completion of parenteral iron therapy was recorded and fatigue score was assessed. The pregnant women were monitored for the adverse events. Results: All pregnant women received a single IV infusion of FCM 1000 mg. A significant increase in the hemoglobin of 2.37±0.51 g/dl (p<0.001) was noted at 4 weeks, MCV rise of 19.89±21.94 (p<0.001) was noted at 4 weeks, MCHC rise was of 2.56±5.65 and PCV rise was of 4.45±2.67 (p<0.011) at over 4 weeks. Significant improvement in fatigue score was observed at 4 weeks after single FCM infusion. No adverse effects were observed in any pregnant woman throughout the duration of the study. Conclusions: This real-life observational study highlights IV FCM is effective in management of IDA in pregnant women and well tolerated. Trial registration number: CTRI/2021/02/030874